Penerapan Arsitektur Tropis pada Bangunan Sekolah Menengah Atas Katolik Frateran Ndao di Kota Ende, Nusa Tenggara Timur - Alfred D.D, Jhon Alfred (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Educational buildings in tropical regions, such as the Frateran Ndao Catholic High School (SMAK) in Ende City, East Nusa Tenggara, are faced with the challenge of achieving thermal and visual comfort due to exposure to direct sunlight, high humidity, and air circulation that is not always optimal. This study was conducted to evaluate the extent to which the principles of tropical architecture are applied to the building of SMAK Frateran Ndao, especially in terms of building orientation, opening system, cross ventilation, natural lighting, as well as shading and overstacking. The research method used is qualitative descriptive, with a case study approach. Data was collected through direct observation of architectural elements, field measurements of building orientation and openings, visual documentation, and interviews with space users (students). The data analysis technique is carried out through an evaluative-qualitative approach, namely by examining the findings of tropical architectural principles which include aspects of orientation to the dominant sun and wind, the effectiveness of cross-ventilation, the adequacy of natural lighting intensity, the role of overstack in ventilation, and the presence of natural shadowing elements in the building environment. The results of the study show that the orientation of the building facing southeast is quite effective in maximizing morning lighting, but it has not been able to reduce excessive heat and glare during the day due to the lack of shade vegetation and limited cross openings. The overstack system has been implemented but has not been supported by other passive elements as a whole. Meanwhile, space users complained of thermal and visual discomfort between 11.00 and 14.00, which can only be temporarily overcome with the use of curtains. Thus, it can be concluded that the application of tropical architectural principles to the SMAK Frateran Ndao building is still limited to basic orientation and ventilation, and has not been fully optimized through a thorough passive design strategy. Therefore, it is necessary to redesign the shadowing elements, add shade tropical vegetation, and improve the cross-opening system to support the comfort of the learning room in accordance with tropical climate conditions in a sustainable manner.